Preparation of spinning type CNT diffusion layer / membrane electrode
By growing a spinning CNT diffusion layer that is wound on carbon paper, the problem of the conventional fuel cell membrane electrodes easily collapse under acidic conditions and high temperature and high voltage and penetration with the catalytic layer is solved, thereby achieving higher durability and electrical conductivity.
Patent Information
- Application Number
- CN202311600769.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2025-06-06
AI Technical Summary
The microporous layer of the traditional fuel cell membrane electrode is prone to collapse under acidic conditions and high temperature and high voltage, and is prone to permeation with the catalytic layer, resulting in the inability to expose the Pt active crystal surface and poor corrosion of the carbon powder, which affects the durability and conductivity of the membrane electrode.
A small molecule organic carbon compound liquid is used as the carbon source, transition metal organic matter is used as the catalyst, and thiophene/carbon disulfide is used as the accelerator. Under the synergistic action of the surfactant, an interwoven spinning CNT diffusion layer is grown on the carbon paper, and impurities are washed away by filtration to form a spinning CNT diffusion layer with high mechanical strength and electrical conductivity.
The conductive and mass transfer capabilities of the diffusion layer are effectively improved, and the disadvantages of the traditional diffusion layer collapse under high temperature and high voltage and mixing with the catalytic layer is avoided, which improves the durability and conductivity of the membrane electrode.
Smart Images

Figure CN120109238A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cells, and in particular to the field of membrane electrodes. Background Art
[0002] The gas diffusion layer (GDL) is an important component of the fuel cell membrane electrode, and it plays an important role in the electrochemical process. It transports hydrogen / oxygen to the reaction area and removes water from the electrode. In order to enhance conductivity, one side of the GDL is usually coated with a microporous layer (MPL). The traditional MPL is usually coated with carbon powder and polytetrafluoroethylene (PTFE) as a hydrophobic agent on one side. However, under the acidic conditions and durable conditions of the fuel cell, the MPL is prone to infiltration with the catalyst layer, making it impossible for Pt to expose the active crystal surface. Carbon powder is easily corroded under high potential conditions, causing the microporous layer structure to collapse.
[0003] The material performance of the carbon nanotube layer is better than that of carbon black, and it has a higher porosity and specific surface area. The present invention uses a small molecule organic carbon compound liquid as a carbon source, a transition metal organic compound as a catalyst, and thiophene / carbon disulfide as a promoter. Under the synergistic effect of a surfactant, the organic carbon source grows mutually entangled spinning-type CNTs on carbon paper under the action of temperature increase and hydrogen reduction. The transition metal organic compound is removed by filtering and washing to obtain a spinning-type CNT diffusion layer grown on carbon paper. The diffusion layer has a strong mechanical structure and conductivity, and can improve the durability and conductivity of the membrane electrode. Summary of the invention
[0004] The present invention prepares a diffusion layer of spun CNT grown on carbon paper, effectively improving the conductivity and mass transfer capacity of the diffusion layer, and effectively avoiding the shortcomings of the traditional diffusion layer collapsing under high temperature and high voltage conditions and mixing with the catalyst layer.
[0005] The present invention provides a method for preparing a spinning type CNT diffusion layer and a membrane electrode, and the process is as follows: (1) Weigh small molecule organic carbon liquid, transition metal catalyst, thiophene / carbon disulfide and surfactant according to the mass ratio to prepare a solution, and stir magnetically for 0.5-1h to mix the solution evenly; (2) placing the solution in a sprayer, spraying the solution onto carbon paper (the carbon paper is placed on a heating plate) according to a preset spraying sequence and spraying rate, and drying the carbon paper; (3) immersing the dried carbon paper in a container containing the organic small molecule carbon liquid, and continuously introducing hydrogen, heating the container to 500-1200° C., and the reaction time is 0.5-1 h; (4) After cooling to room temperature, taking out the carbon paper, filtering it with deionized water to remove impurities, and drying the carbon paper at 200° C. to 350° C.; (5) Cutting and drying the carbon paper into a cathode diffusion layer and an anode diffusion layer, laminating the anode diffusion layer, the catalyst-supported membrane (CCM), and the cathode diffusion layer in a preset order, and hot pressing them to obtain a final membrane electrode (MEA).
[0006] Optionally, in step (1), the mass ratio of the small molecule organic carbon liquid, the transition metal catalyst, the thiophene / carbon disulfide and the surfactant is (95-99): (0.2-0.5): (0.1-0.5): (0.1-3).
[0007] Optionally, in step (1), the organic small molecule carbon liquid is one or any combination of ethanol, propanol, butanol or acetone.
[0008] Optionally, in step (1), the transition metal catalyst includes one or any combination of ferrocene, ferric nitrate, nickel nitrate, and cobalt nitrate.
[0009] Optionally, in step (1), the surfactant is an ionic surfactant including sodium lignin sulfonate, sodium dodecyl sulfonate, cetyltrimethylammonium bromide (CTAB) or a non-ionic surfactant including one or any combination thereof.
[0010] Preferably, in step (2), the spraying speed is 10-15 mm / s on the X axis and 10-20 mm / s on the Y axis, the spraying order is from left to right and from top to bottom, the number of spraying times is 2-5 times, and the temperature of the heating plate is 100-200°C.
[0011] Preferably, in step (3), the flow rate of hydrogen is 800-1200 sccm.
[0012] Optionally, in step (5), the CCM is Hongji SER350 or Hongji XER350.
[0013] Preferably, in step (5), the hot pressing time is 90-120 s, the hot pressing temperature is 90-120° C., and the hot pressing pressure is 90-120 MPa.
[0014] Compared with the prior art, the present invention has the following advantages: (1) CNTs have high mechanical strength and conductivity. The spun CNTs grown on carbon paper avoid the collapse of traditional microporous layers of carbon black.
[0015] (2) The diffusion layer is used on the membrane electrode to cooperate with the catalytic layer to better complete the conduction of gas, protons and water, form an effective three-phase interface, reduce the activation time, and improve the durability of the membrane electrode.
[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 The spinning type CNT synthesized in Example 1; Figure 2 Comparative table of conductivity of diffusion layers of embodiments and comparative examples; Figure 3 100h polarization curve test of durability of the embodiments and comparative examples. Implementation
[0018] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.
[0019] The preparation method of the present invention will be described below with reference to the accompanying drawings, wherein Figure 1 The spinning type CNT synthesized in Example 1; Figure 2 Comparative table of conductivity of diffusion layers of embodiments and comparative examples; Figure 3 100h polarization curve test of durability of the embodiments and comparative examples.
[0020] According to an embodiment of the method for preparing a spinning type CNT diffusion layer / membrane electrode of the present invention, the method comprises: (1) Weigh small molecule organic carbon liquid, transition metal catalyst, thiophene / carbon disulfide and surfactant according to the mass ratio to prepare a solution, and stir magnetically for 0.5-1h to mix the solution evenly; (2) placing the solution in a sprayer, spraying the solution onto carbon paper (the carbon paper is placed on a heating plate) according to a preset spraying sequence and spraying rate, and drying the carbon paper; (3) immersing the dried carbon paper in a container containing the organic small molecule carbon liquid, and continuously introducing hydrogen, heating the container to 500-1200° C., and the reaction time is 0.5-1 h; (4) After cooling to room temperature, taking out the carbon paper, filtering it with deionized water to remove impurities, and drying the carbon paper at 200° C. to 350° C.; (5) Cutting and drying the carbon paper into a cathode diffusion layer and an anode diffusion layer, laminating the anode diffusion layer, the catalyst-supported membrane (CCM), and the cathode diffusion layer in a preset order, and hot pressing them to obtain a final membrane electrode (MEA).
[0021] According to some embodiments of the present invention, in step (1), the mass ratio of the small molecule organic carbon liquid, the transition metal catalyst, the thiophene / carbon disulfide and the surfactant is (95-99): (0.2-0.5): (0.1-0.5): (0.1-3).
[0022] According to some embodiments of the present invention, in step (1), the organic small molecule carbon liquid is one or any combination of ethanol, propanol, butanol or acetone.
[0023] According to some embodiments of the present invention, in step (1), the transition metal catalyst includes one or any combination of ferrocene, ferric nitrate, nickel nitrate, and cobalt nitrate.
[0024] According to some embodiments of the present invention, in step (1), the surfactant is an ionic surfactant including sodium lignin sulfonate, sodium dodecyl sulfonate, cetyltrimethylammonium bromide (CTAB) or a non-ionic surfactant including polysorbate or any combination thereof.
[0025] According to some embodiments of the present invention, in step (2), the spraying speed is 10-15 mm / s on the X axis and 10-20 mm / s on the Y axis, the spraying order is from left to right and from top to bottom, the number of spraying is 2-5 times, and the temperature of the heating plate is 100-200°C.
[0026] According to some embodiments of the present invention, in step (3), the flow rate of hydrogen is 800-1200 sccm.
[0027] According to some embodiments of the present invention, in step (5), the CCM is Hongji SER350 or Hongji XER350.
[0028] According to some embodiments of the present invention, in step (5), the hot pressing time is 90-120 s, the hot pressing temperature is 90-120° C., and the hot pressing pressure is 90-120 MPa.
[0029] According to an embodiment of the present invention: 9.5g acetone, 0.05g ferrocene, 0.03g thiophene and 0.3g CTAB are weighed and placed in a beaker, and mixed by magnetic stirring for 0.5h. The mixed solution is placed in a nozzle with a nozzle speed of 10mm / s on the X axis and 20mm / s on the Y axis, and sprayed onto Toray's carbon paper, and the liquid on the carbon paper is dried in time at 120°C. The dried carbon paper is immersed in a container filled with acetone, and hydrogen is introduced into the container at a ventilation rate of 1000sccm. The container is heated to 800°C and reacted for 0.5h. After cooling to room temperature, the carbon paper is taken out, washed with a large amount of deionized water, and then dried under vacuum conditions at 200°C to obtain the final spinning-type CNT diffusion layer; Cut the diffusion layer to obtain the cathode diffusion layer and the anode diffusion layer, arrange the cathode diffusion layer, XER350 CCM, and the anode diffusion layer in sequence, and use a hot pressing temperature of 90°C, a hot pressing time of 100s, and a hot pressing pressure of 100MPa to obtain the final MEA; Test of the conductivity of the diffusion layer: The RTS-9 dual-electricity four-probe measuring instrument is used to measure the conductivity of the diffusion layer. In order to eliminate the contact resistance between the metal probe and the sample, the DC four-probe method is directly used to test the conductivity; Membrane electrode polarization test: 30A-570A as scanning current density, running for 30s at each current, current ramp rate of 15A / s, anode stoichiometric ratio of 2.2, cathode stoichiometric ratio of 3.5. Anode humidity 40% RH, cathode humidity 60% RH, hydrogen back pressure 120 kPa, air back pressure 100kPa, anode 75℃, cathode 75℃, stack temperature 78℃.
[0030] According to an embodiment of the present invention: 8g of ethanol, 0.04g of cobalt nitrate, 0.04g of carbon disulfide, and 0.08g of polysorbate are weighed and placed in a beaker, and mixed by magnetic stirring for 1h. The mixed solution is placed in a nozzle with a nozzle speed of 15mm / s on the X axis and 10mm / s on the Y axis, and sprayed onto Toray's carbon paper, and the liquid on the carbon paper is dried in time at 100°C. The dried carbon paper is immersed in a container filled with ethanol, and hydrogen is introduced into the container at a ventilation rate of 1200sccm. The container is heated to 900°C and reacted for 0.5h. After cooling to room temperature, the carbon paper is taken out, washed with a large amount of deionized water, and then dried under vacuum conditions at 300°C to obtain the final spinning-type CNT diffusion layer; Cut the diffusion layer to obtain the cathode diffusion layer and the anode diffusion layer, arrange the cathode diffusion layer, SER350 CCM, and the anode diffusion layer in sequence, and use a hot pressing temperature of 100°C, a hot pressing time of 120s, and a hot pressing pressure of 90MPa to obtain the final MEA; According to an embodiment of the present invention: 9.3 g of acetone, 0.03 g of nickel nitrate, 0.03 g of carbon disulfide, and 0.18 g of sodium lignin sulfonate are weighed and placed in a beaker, and mixed by magnetic stirring for 1 hour. The mixed solution is placed in a nozzle with a nozzle speed of 10 mm / s on the X axis and 20 mm / s on the Y axis, and sprayed onto Toray's carbon paper, and the liquid on the carbon paper is dried in time at 100°C. The dried carbon paper is immersed in a container filled with ethanol, and hydrogen is introduced into the container at a ventilation rate of 1100 sccm. The container is heated to 1200°C and reacted for 0.5 hours. After cooling to room temperature, the carbon paper is taken out, washed with a large amount of deionized water, and then dried under vacuum conditions at 250°C to obtain the final spinning-type CNT diffusion layer; The diffusion layer was cut to obtain a cathode diffusion layer and an anode diffusion layer. The cathode diffusion layer, XER350 CCM, and anode diffusion layer were arranged in sequence. The hot pressing temperature was 110° C., the hot pressing time was 90 s, and the hot pressing pressure was 100 MPa to obtain the final formed MEA.
[0031] A comparative example corresponding to this case: 5.9 g of carbon black XC-72 was weighed, dissolved in 100 ml of acetone, and stirred by magnetic force for 0.5 h, and the mixed solution was placed in the nozzle. The mixed solution was placed in the nozzle, and the nozzle speed was 10 mm / s on the X axis and 20 mm / s on the Y axis, and sprayed onto Toray's carbon paper, and the liquid on the carbon paper was dried in time at 120°C. The diffusion layer of the comparative example was obtained; The diffusion layer was cut to obtain a cathode diffusion layer and an anode diffusion layer, and the cathode diffusion layer, XER350 CCM, and anode diffusion layer were arranged in sequence, and a hot pressing temperature of 90° C., a hot pressing time of 100 s, and a hot pressing pressure of 100 MPa were used to obtain the final formed MEA.
[0032] in, Figure 1 The TEM image of the diffusion layer proves that under the action of the catalyst and the promoter, the spinning type CNTs are grown on the carbon paper and entangled with each other (the white dots are transition metals), so that the microporous layer has high mechanical strength and porosity, which is conducive to the discharge of gas and water. By comparing the conductivity of the embodiment and the comparative example, it is proved that CNT has a strong conductivity. After being applied to carbon paper, its average conductivity is 650S / cm. After 100h durability test, the polarization curve analysis shows that the voltage of comparative example 1 drops sharply when the current density is 0.6A / cm2, which indirectly proves that under high potential conditions, the carbon structure collapses, causing the performance of the membrane electrode to decrease. Compared with the open circuit voltage, the embodiment has a higher open circuit voltage. Under the condition of 0.65V rated power, the current density of Example 2 is 1.86A / cm2. The membrane electrode prepared by this method can not only greatly reduce the activation time, but also establish a good three-phase reaction interface, and has high commercial value and application prospects.
[0033] Any reference to "one embodiment," "an embodiment," "an illustrative embodiment," etc., means that a specific component, structure, or feature described in connection with the embodiment is included in at least one embodiment of the present invention. Such illustrative expressions throughout this specification do not necessarily refer to the same embodiment. Moreover, when a specific component, structure, or feature is described in connection with any embodiment, it is claimed that it is within the scope of those skilled in the art to implement such component, structure, or feature in connection with other embodiments.
[0034] Although specific embodiments of the present invention have been described in detail with reference to a number of illustrative embodiments of the present invention, it must be understood that a variety of other modifications and embodiments may be devised by those skilled in the art that will fall within the spirit and scope of the principles of the present invention. Specifically, within the scope of the foregoing disclosure, drawings, and claims, reasonable variations and improvements may be made in the arrangement of parts, modules, and / or their subordinate combination layouts without departing from the spirit of the present invention. Except for variations and improvements in parts, modules, and / or layouts, the scope thereof is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a spinning type CNT diffusion layer / membrane electrode, the process is as follows: (1) Weigh small molecule organic carbon liquid, transition metal catalyst, thiophene / carbon disulfide and surfactant according to the mass ratio to prepare a solution, and stir magnetically for 0.5-1h to mix the solution evenly; (2) placing the solution in a sprayer, spraying the solution onto carbon paper according to a preset spraying sequence and spraying rate, and drying the carbon paper; (3) immersing the dried carbon paper in a container containing the organic small molecule carbon liquid, and continuously introducing hydrogen, heating the container to 500-1200° C., and the reaction time is 0.5-1 h; (4) After cooling to room temperature, taking out the carbon paper, filtering it with deionized water to remove impurities, and drying the carbon paper at 200° C. to 350° C.; (5) Cutting and drying the carbon paper into a cathode diffusion layer and an anode diffusion layer, laminating the anode diffusion layer, the catalyst-supported membrane (CCM), and the cathode diffusion layer in a preset order, and hot pressing them to obtain a final membrane electrode (MEA).
2. A method for preparing a spinning type CNT diffusion layer / membrane electrode according to claim 1, It is characterized in that In step (1), the mass ratio of the small molecule organic carbon liquid, the transition metal catalyst, the thiophene / carbon disulfide and the surfactant is (95-99): (0.2-0.5): (0.1-0.5): (0.1-3).
3. According to the method for preparing a spinning type CNT diffusion layer / membrane electrode in right 1, in step (1), the organic small molecule carbon liquid is one or any combination of ethanol, propanol, butanol or acetone.
4. According to the method for preparing a spun CNT diffusion layer / membrane electrode in claim 1, in step (1), the transition metal catalyst includes one or any combination of ferrocene, ferric nitrate, nickel nitrate, and cobalt nitrate.
5. According to the method for preparing a spun CNT diffusion layer / membrane electrode in right 1, in step (1), the surfactant is an ionic surfactant including sodium lignin sulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide (CTAB) or a non-ionic surfactant such as polysorbate or any combination thereof.
6. According to the method for preparing a spun CNT diffusion layer / membrane electrode in right 1, in step (2), the spraying speed is 10-15 mm / s on the X axis and 10-20 mm / s on the Y axis, the spraying order is from left to right and from top to bottom, and the number of spraying times is 2-5 times.
7. According to the method for preparing a spinning type CNT diffusion layer / membrane electrode in claim 1, in step (3), the flow rate of the hydrogen is 800-1200 sccm.
8. According to the method for preparing a spun CNT diffusion layer / membrane electrode in claim 1, in step (5), the CCM is Hongji SER350 or Hongji XER350.
9. According to the method for preparing a spun CNT diffusion layer / membrane electrode in right 1, in step (5), the hot pressing time is 90-120s, the hot pressing temperature is 90-120°C, and the hot pressing pressure is 90-120MPa.